No argument for God : going beyond reason in conversations about faith - Wilkinson, John. (Downers Grove, Ill. : IVP Books, 2011)
Religion is irrational! New atheists trumpet the claim loudly, so much so that it's become a sort of conventional wisdom. Professing your faith in God sounds increasingly like a confession of intellectual feebleness. Belief in God sounds as cute and quaint as it does pointless. John Wilkinson contends that the irrationality of faith is its greatest asset, because rationalism itself sets artificial limits on all that we've seen -- which itself is hinting at something greater that can't be seen. In No Argument for God he turns the tables on the cult of reason, showing that it limits conversation to what happened, when what we really want is the why behind it. We settle for investigation when what we need is revelation -- the answer to all our longings. Read this book and break though the gridlock of apologetic arguments to a life-giving encounter with the God who satisfies our minds and seeks our good. - Publisher.
Wouldn't it be nice? -- Seeing things for the first time -- Stop making sense -- Two-dimensional existence -- All in your head -- Guess who is at the door -- In the flesh -- No stranger to nonsense -- Circular reasoning -- Dialogue -- Discontent -- Echoes of God -- What can I say? -- The dream of God.
Includes bibliographical references (pages [171]-173).
Description based on print version record.
Keywords: Faith and reason -- Christianity; Apologetics; Apologetics; Faith and reason -- Christianity; RELIGION / Christian Theology / General; Electronic books